2022
DOI: 10.3389/fcvm.2021.798897
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Hospitalized Patients With COVID-19 With Acute Kidney Injury and Acute Cardiac Injury

Abstract: PurposeThis study investigated the incidence, disease course, risk factors, and mortality in COVID-19 patients who developed both acute kidney injury (AKI) and acute cardiac injury (ACI), and compared to those with AKI only, ACI only, and no injury (NI).MethodsThis retrospective study consisted of hospitalized COVID-19 patients at Montefiore Health System in Bronx, New York between March 11, 2020 and January 29, 2021. Demographics, comorbidities, vitals, and laboratory tests were collected during hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…A novelty of our study is the longitudinal assessment of medical subspecialty care received by COVID-19 survivors at follow-up. The high rates of pulmonologist, cardiologist, and nephrologist, neurologist, and vascular medicine visits are consistent with commonly reported organ system involvement in acute COVID-19 [ 41 46 ]. Some of these medical usages could be associated with ongoing medical needs which might have been exacerbated by COVID-19, while others were associated with new subspecialist needs due to new problems caused by COVID-19.…”
Section: Discussionsupporting
confidence: 70%
“…A novelty of our study is the longitudinal assessment of medical subspecialty care received by COVID-19 survivors at follow-up. The high rates of pulmonologist, cardiologist, and nephrologist, neurologist, and vascular medicine visits are consistent with commonly reported organ system involvement in acute COVID-19 [ 41 46 ]. Some of these medical usages could be associated with ongoing medical needs which might have been exacerbated by COVID-19, while others were associated with new subspecialist needs due to new problems caused by COVID-19.…”
Section: Discussionsupporting
confidence: 70%
“…All data originated from observational databases in the Montefiore Health System as described in previous reports (Hoogenboom, Fleysher, et al., 2021 ; Hoogenboom, Pham, et al., 2021 ; Lu, 2021 ; Lu et al., 2022 ). Briefly, patient data between January 1, 2020, and June 9, 2021, were standardized to the Observational Medical Outcomes Partnership (OMOP) Common Data Model (CDM) version 6, which uses standard vocabulary concepts, allowing for the systematic analysis of disparate observational databases such as electronic medical records and disease classification systems (e.g., ICD‐10, SNOWMED, LOINC) (Hripcsak et al., 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported the rate of cardiac injury and mortality in COVID-19 patients. Contextually, Lu and coworkers determined that 9.45% of the patients with COVID-19 experienced cardiac injury, and the mortality was 29.6% [ 14 ]. Moreover, Fan et al reported that the prevalence of cardiac injury was 16.44%, and the mortality rate of 64.4% among 73 patients with COVID-19 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%